TYPES OF FIGURATIVE LANGUAGE AND MEANING FOUND IN THE NOVEL “THE CLIENT” BY JOHN GRISHAM - Gajung, Maria Angela (ID Solutions, 2023)
The tittle of this research is types of figurative language found in the novel “The Client” by John Grisham. The purpose of this research is to identify the types of figurative language and analyse the meaning in the novel. This research also uses a qualitative descriptive method using two theories. The first is the figurative language theory to identify the types of figurative language from the novel “The Client” proposed by Knickerbocker & Renninger (1963), and the second theory by Leech (1981) to analyse the meaning of figurative language. The focus of this research was to figure out what kinds of figurative language found in the novel “The Client” by John Grisham. There are two research problem of the study namely: (1) What are the types of figurative language are found in the novel “The Client” by John Grisham, (2) What is the meanings of each types of figurative language found in the novel “The Client” by John Grisham. The results of this study indicate that there are four types of figurative language found in the novel “The Client”, namely simile, personification, and metaphor. Here the dominant type is Simile.